It’s Showtime! Improving Agricultural Productivity through TV Programming and Improved Input Access - Robinson, Jonathan; Aggarwal, Shilpa; Kramer, Berber; Ceballos, Francisco (American Economic Association, 2023)
Television is a powerful tool to scale ‘edutainment’ - information that is both educational and entertaining. One such form of information is agricultural information, but there is limited rigorous evidence on the effect of extension delivered via television on agricultural outcomes, such as investment or productivity. Moreover, while television can provide easy access to information, its impact on agricultural investment may be constrained by other barriers, such as market access. We implement a cross-randomized experiment to simultaneously address information and market access constraints. We will evaluate a new farm makeover show broadcast on national TV in Zambia called “Munda Make Over”, modeled after the popular Kenyan show “Shamba Shape Up”. The show is similar to home makeover shows in developed countries, featuring visits by an expert who tours the farm, points out areas for improvement, and implements their advice, with segments dedicated to gender issues interspersed throughout the season. To address market access, we simultaneously cross-randomize “road shows”, locally-held events in which providers make their products and services available for sale closer to where farmers live, addressing barriers to market access. The road show will feature inputs such as seeds of improved, drought-resistant varieties, or other relevant inputs. MMO partners may also use the road shows to provide other products and services designed for smallholder farmers, for instance, agricultural credit or crop insurance.